2013
DOI: 10.3357/asem.3394.2013
|View full text |Cite
|
Sign up to set email alerts
|

Changed Joint Position Sense and Muscle Activity in Simulated Weightlessness by Water Immersion

Abstract: Proprioceptive feedback for active arm movements is enhanced under water, probably due to high water viscosity, which increases spindle afferents during active but not passive arm movements or isometric responses. We found no evidence that the reference frame for orientation judgments differ between Wet and Dry. Muscle tone of the relaxed arm was reduced under water, corroborating that water immersion degrades proprioception during isometric tasks and passive arm positioning. This is probably not relevant for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…This fi nding speaks again for an incorrect proprioception and led us to conclude that quick and complete feedback error corrections were not suffi ciently available. Indeed, proprioceptive changes under water are well known: previous studies reported a changed joint positioning sense ( 2 ), a changed muscular tone ( 9 ), and releases of inhibitory neuromuscular circuits ( 24 ) under shallow water immersion conditions. All of those neuronal changes indisputably contribute to the quality of proprioceptive feedback signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fi nding speaks again for an incorrect proprioception and led us to conclude that quick and complete feedback error corrections were not suffi ciently available. Indeed, proprioceptive changes under water are well known: previous studies reported a changed joint positioning sense ( 2 ), a changed muscular tone ( 9 ), and releases of inhibitory neuromuscular circuits ( 24 ) under shallow water immersion conditions. All of those neuronal changes indisputably contribute to the quality of proprioceptive feedback signals.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to these underwater data, an increase was observed already for initial force during visual fi eld motion (+42%), in hypergravity (+140%), and in microgravity (+20%). We attributed this early increase to erroneous central motor planning, possibly due to changed vestibulospinal activity ( 6 , 15 , 22 ); conversely, the lack of an early increase in the underwater study argues against motor planning problems in that environment, and rather suggests defi cits of proprioceptive feedback, possibly due to a changed muscular tone ( 9 ).…”
mentioning
confidence: 96%
“…However, recent studies have shown that arm kinematics vary for movements performed along different directions in the vertical plane (i.e., with and against the direction of the gravity vector) in a manner that is consistent with an optimization of both inertial and gravitational forces (Papaxanthis et al, 2003 ; Gentili et al, 2007 ; Le Seac’h and Mcintyre, 2007 ; Berret et al, 2008 ). Moreover, other work suggests that anticipating such gravitational effects on the arm depends strongly on input from the proprioceptive system (Soechting, 1982 ; Soechting and Ross, 1984 ; Worringham and Stelmach, 1985 ; Worringham et al, 1987 ; Swinnen et al, 1997 ; Lemay et al, 2004 ; Proske, 2005 ; Dalecki and Bock, 2013 ). This raises the possibility that proprioceptive abilities could also differ for movements performed along different directions in the vertical plane, more specifically as a function of direction with respect to the gravitational vector.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the synchronized swimmers had better underwater ankle joint proprioception than the controls, suggesting that the skin receptors responsible for the accurate spatial positioning of body parts underwater and central processing of these sensory signals (Counil, 2015) were also enhanced through synchronized swimming. Another plausible explanation is that a number of synchronized swimming techniques require forceful ankle plantarflexion against water resistance to maintain body balance (e.g., eggbeater movement) (Homma & Homma, 2005), which may increase the muscle spindle afferents and, hence, underwater ankle joint proprioception (Dalecki & Bock, 2013).…”
Section: Discussionmentioning
confidence: 99%